Polyester film
By using a polyester film with furanyl dicarboxylic acid as the main component, and controlling the orientation coefficient, haze, and cyclic dimer content, the problem of decreased transparency of polyester film during heating was solved, enabling the application of polyester film that maintains transparency at high temperatures.
Patent Information
- Application Number
- CN202480020505.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-24
- Filing Date
- 2024-02-28
- Publication Date
- 2025-10-21
AI Technical Summary
Existing polyester films are prone to whitening during heat treatment, resulting in decreased transparency and making them unsuitable for applications requiring high transparency, such as food packaging and optical applications.
A polyester film with furanyl dicarboxylic acid as the main component is used. By controlling the surface orientation coefficient, haze, cyclic dimer content and lamination structure, the transparency of the polyester film is not easily reduced when heated.
This technology enables polyester films to maintain high transparency even under heating conditions, making them suitable for industrial and packaging applications.
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to a polyester film having furandicarboxylic acid units. Background Art
[0002] Polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), thermoplastic resins with excellent heat resistance and mechanical properties, are used in a wide variety of fields, including plastic films, electronic devices, energy, packaging materials, and automobiles. Among plastic films, biaxially oriented PET film is widely used in industrial and packaging applications due to its excellent balance of mechanical properties, heat resistance, dimensional stability, chemical resistance, optical properties, and cost.
[0003] In recent years, resins made from biomass-derived raw materials have attracted significant attention as environmentally sustainable materials, driven by the desire to break free from dependence on petroleum. Poly(ethylene furandicarboxylate) (PEF), due to its planar structure and the presence of biomass-derived furandicarboxylic acid (FDCA), is attracting attention as a renewable resin that promises to offer heat resistance equal to or superior to that of conventional petroleum-derived resins such as polyethylene terephthalate (PET). Furthermore, PEF can easily utilize both its carboxylic acid and diol components as biomass-derived raw materials.
[0004] A polyester film has been proposed. A resin composed of a dicarboxylic acid component primarily composed of furandicarboxylic acid and a diol component primarily composed of ethylene glycol is biaxially stretched. The resulting film has a plane orientation coefficient within a specific range and exhibits mechanical strength and dimensional stability sufficient for industrial applications, packaging, and the like (Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 6440336
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 2022-155579 Summary of the Invention
[0009] Problems to be solved by the invention
[0010] Although Patent Document 1 discloses a polyester film having excellent mechanical strength, it is known to have the following problem: the polyester film whitens when heated, making it difficult to use in applications requiring high transparency, such as food packaging films and optical applications.
[0011] The present inventors speculate that low-molecular-weight components contained in the polyester film cause the film to whiten. For example, Patent Document 2 discloses a polyester resin having 2,5-furandicarboxylic acid units and ethylene glycol units, as a polyester resin having reduced cyclic dimers as low-molecular-weight components. It is conceivable that the polyester resin described in Patent Document 2 could be used to produce polyester films.
[0012] However, the polyester resin described in Patent Document 2 fails to sufficiently reduce cyclic dimers. Furthermore, when producing films, the polyester resin is remelted during the melt extrusion process, but a large amount of cyclic dimers is generated during the remelting process. When heated, films produced from the polyester resin described in Patent Document 2 precipitate the cyclic dimers contained in the polyester resin onto the film surface, resulting in severe whitening of the film, making it difficult to use in industrial films or packaging films.
[0013] An object of the present invention is to provide a polyester film using biomass-derived furandicarboxylic acid, wherein the polyester film has a low cyclic dimer content and is less likely to exhibit a decrease in transparency even when heated.
[0014] Means used to solve problems
[0015] That is, the present invention includes the following inventions.
[0016] [1] A polyester film comprising a dicarboxylic acid component mainly composed of furandicarboxylic acid and a diol component mainly composed of ethylene glycol, wherein the polyester film satisfies the following necessary conditions (1) to (3):
[0017] (1) The plane orientation coefficient ΔP is greater than or equal to 0.100 and less than or equal to 0.170;
[0018] (2) The haze of the polyester film is less than 15%;
[0019] (3) The haze of the polyester film is denoted as Hz0 (%), and the haze of the polyester film after heating the polyester film at 150° C. for 30 minutes is denoted as Hz. 30 (%), satisfying Hz 30 -Hz0≤15.
[0020] [2] The polyester film according to [1] further satisfies the following necessary condition (4):
[0021] (4) The content of cyclic dimers is 1.0% by mass or less.
[0022] [3] The polyester film according to [1] further satisfies the following requirements (5) and (6):
[0023] (5) Having a stacked structure of more than three layers;
[0024] (6) The content of the cyclic dimer in at least one surface is 1.0% by mass or less.
[0025] Effects of the Invention
[0026] The polyester film of the present invention is a polyester film having biomass-derived furandicarboxylic acid units, has a low cyclic dimer content, and is less likely to exhibit a decrease in transparency even when heated. Therefore, the polyester film can be suitably used as an industrial film or a packaging film. DETAILED DESCRIPTION
[0027] The polyester film of the present invention is formed from a dicarboxylic acid component primarily composed of furandicarboxylic acid and a diol component primarily composed of ethylene glycol. Specifically, the polyester film of the present invention is produced using a polyethylene furandicarboxylate resin primarily composed of furandicarboxylic acid as the dicarboxylic acid component and primarily composed of ethylene glycol as the diol component. The terms "primarily" and "primarily" herein mean that furandicarboxylic acid accounts for 80 mol% or more of 100 mol% of the total dicarboxylic acid component, and that ethylene glycol accounts for 80 mol% or more of 100 mol% of the total diol component. Of the total dicarboxylic acid component, furandicarboxylic acid preferably accounts for 90 mol% or more, and more preferably 95 mol% or more. Of the total diol component, ethylene glycol preferably accounts for 90 mol% or more, and more preferably 95 mol% or more.
[0028] As long as the purpose of the present invention is not impaired, dicarboxylic acid components other than furandicarboxylic acid and diol components other than ethylene glycol may be copolymerized. The copolymerization amount of the dicarboxylic acid component other than furandicarboxylic acid is less than 20 mol%, preferably less than 10 mol%, and particularly preferably less than 5 mol%, relative to the total dicarboxylic acid components. The copolymerization amount of the diol component other than ethylene glycol is less than 20 mol%, preferably less than 10 mol%, and particularly preferably less than 5 mol%, relative to the total diol components.
[0029] Examples of the dicarboxylic acid component other than furandicarboxylic acid include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, 4,4'-dicarboxybiphenyl, and 5-sodium sulfoisophthalic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 2,5-norbornene dicarboxylic acid, and tetrahydrophthalic acid; and aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, octadecanedioic acid, fumaric acid, maleic acid, itaconic acid, mesaconic acid, citraconic acid, and dimer acid.
[0030] Examples of the diol component other than ethylene glycol include aliphatic diols such as 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 2-amino-2-ethyl-1,3-propanediol, 2-amino-2-methyl-1,3-propanediol, 1,10-decanediol, dimethyloltricyclodecane, diethylene glycol, and triethylene glycol; ethylene oxide adducts or propylene oxide adducts of bisphenol A, bisphenol S, bisphenol C, bisphenol Z, bisphenol AP, and 4,4'-biphenol; and alicyclic diols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol.
[0031] <Polyethylene furandicarboxylate resin>
[0032] As a polymerization method for polyethylene furandicarboxylate-based resins, any production method can be utilized, such as a direct polymerization method in which furandicarboxylic acid is directly reacted with ethylene glycol and, if necessary, other dicarboxylic acid components and diol components, and an ester exchange method in which dimethyl ester of furandicarboxylic acid (including, if necessary, dimethyl ester of other dicarboxylic acids) is ester exchanged with ethylene glycol (including, if necessary, other diol components).
[0033] The intrinsic viscosity of the polyethylene furandicarboxylate resin is preferably 0.30 dl / g to 1.20 dl / g, more preferably 0.55 dl / g to 1.00 dl / g, and even more preferably 0.70 dl / g to 0.95 dl / g. If the intrinsic viscosity is less than 0.30 dl / g, there is a risk of the polyester film cracking. On the other hand, if the intrinsic viscosity is higher than 1.20 dl / g, there is a risk that the filtration pressure increases, making high-precision filtration difficult, making it difficult to squeeze the resin through the filter, or the effect of improving mechanical properties may reach saturation.
[0034] The cyclic dimer content in the polyethylene furandicarboxylate resin is preferably 1.0% by mass or less, more preferably 0.7% by mass or less, and even more preferably 0.5% by mass or less. During the extrusion process during film production, the polyethylene furandicarboxylate resin is melted, but cyclic dimers are regenerated during melting. Therefore, the cyclic dimer content in the polyethylene furandicarboxylate resin is preferably 1.0% by mass or less. The lower the cyclic dimer content in the polyethylene furandicarboxylate resin, the better. However, due to technical difficulties, the lower limit is 0.1% by mass.
[0035] <Additives>
[0036] The polyester film of the present invention may contain additives as long as they do not impair the purpose of the present invention. The additives used in the present invention can be selected from inorganic particles, organic particles, inactive particles such as heat-resistant polymer particles and cross-linked polymer particles, fluorescent brighteners, ultraviolet light blockers, infrared absorbing pigments, surfactants, antioxidants, thermal stabilizers, and the like, depending on the intended use. The additives may be present in a single type or in combination of two or more. The timing of adding the additives is not particularly limited, as long as it does not impair the physical properties of the resulting polyester film.
[0037] The inactive particles are preferably at least one selected from inorganic particles and organic particles. Any inorganic particle may be selected as the inorganic particle, for example, silica, calcium carbonate, barium sulfate, calcium sulfate, aluminum oxide, kaolinite, talc, etc. In particular, from the perspective of transparency, silica particles, particularly amorphous silica particles, having a refractive index close to that of the resin component are preferred.
[0038] The average particle size of the above-mentioned inorganic particles is preferably 1 to 10 μm, more preferably 1.5 to 7 μm, and further preferably 2 to 5 μm. If the average particle size of the inorganic particles is 1 μm or more, a concave-convex structure suitable for imparting slipperiness can be imparted to the surface. On the other hand, if the average particle size of the inorganic particles is 10 μm or less, high transparency can be maintained. In addition, the content of inactive particles in polyester is preferably 0.005 to 1.0 mass %, more preferably 0.008 to 0.5 mass %. If the content of microparticles is 0.005 mass % or more, a concave-convex structure suitable for imparting slipperiness can be imparted to the surface of the surface layer. On the other hand, if the content of microparticles is 1.0 mass % or less, high transparency can be maintained.
[0039] Any UV absorber can be selected from known UV absorbers depending on the intended use. Examples of UV absorbers include organic UV absorbers such as benzotriazole compounds and benzophenone compounds, and inorganic UV absorbers such as zinc oxide, titanium oxide, and cerium oxide in microparticle form with a particle size of 0.2 μm or less. Any antioxidant can be selected, including aromatic amines and phenols. Thermal stabilizers include phosphorus-based (such as phosphoric acid and phosphate esters), sulfur-based, and amine-based.
[0040] <Physical Properties of Polyester Film>
[0041] The intrinsic viscosity of the polyester film of the present invention is preferably from 0.30 dl / g to 1.20 dl / g, more preferably from 0.40 dl / g to 1.00 dl / g, and even more preferably from 0.50 dl / g to 0.80 dl / g. If the intrinsic viscosity is less than 0.30 dl / g, there is a risk of the polyester film cracking. On the other hand, if the intrinsic viscosity exceeds 1.20 dl / g, there is a risk that the effect of improving mechanical properties will reach saturation.
[0042] The plane orientation coefficient ΔP of the polyester film of the present invention is 0.100 to 0.170, preferably 0.110 to 0.160, and more preferably 0.120 to 0.160. The plane orientation coefficient can be calculated using the following formula by measuring the refractive index nx in the machine direction (MD), the refractive index ny in the direction perpendicular to the machine direction (TD), and the refractive index nz in the thickness direction within the film plane using an Abbe refractometer in accordance with JIS K 7142-1996 5.1 (Method A) using sodium D-rays as the light source.
[0043] ΔP={(nx+ny)-2nz} / 2
[0044] Both nx and ny are preferably 1.570 or greater, more preferably 1.580 or greater, further preferably 1.590 or greater, even more preferably 1.600 or greater, particularly preferably 1.610 or greater, and most preferably 1.620 or greater. By setting nx and ny to 1.570 or greater, sufficient film breaking strength and elongation at break can be achieved, thereby achieving adequate mechanical properties for the film, facilitating post-processing such as film printing and bag making, and making it less likely that the film will break on a printer or coater during subsequent printing or coating, thus being preferred. It should be noted that, from the perspective of manufacturing and thermal shrinkage, nx and ny are preferably less than 1.700.
[0045] The polyester film of the present invention has a haze of 15% or less. A haze of 15% or less reduces film cloudiness, making it easier to inspect contents for defects in food packaging applications. The haze is preferably 10% or less, more preferably 8% or less, even more preferably 5% or less, and particularly preferably 3% or less. A lower haze is preferred, but based on the inherent refractive index of the polyester film, the lower limit is, for example, 0.1%.
[0046] The haze of the polyester film of the present invention is denoted as Hz0 (%), and the haze after the polyester film is heated at 150° C. for 30 minutes is denoted as Hz. 30 (%), from HZ 30The value ΔHz obtained by subtracting HZ0 is 15% or less, preferably 13% or less, and more preferably 10% or less. The polyester film of the present invention has a haze of 15% or less and ΔHz of 15% or less, so the transparency is excellent and the whitening of the film when heated is suppressed. If ΔHz is greater than 15%, when heat treatment is performed in the post-processing of the film, cyclic dimers precipitate, contaminating the process, making it difficult to use as a packaging film or an industrial film. On the contrary, when ΔHz is 15% or less, even if heat treatment is performed in the post-processing, it is not easy to contaminate the process, and the whitening of the film is suppressed, so it can be used as a packaging film or an industrial film. The lower limit of ΔHz is not particularly limited, but from the technical difficulty, it is, for example, 0% or more, preferably 2% or more.
[0047] HZ 30 The value of (the haze after heating the polyester film at 150°C for 30 minutes) is preferably 18% or less, more preferably 15% or less, and further preferably 12% or less. 30 When the HZ content is 18% or less, even if heat treatment is performed in post-processing, the process is less likely to be contaminated, and the whitening of the film is suppressed, so it is easy to use as a packaging film or an industrial film. 30 The lower limit of is not particularly limited, but is, for example, 1% or more due to technical difficulties.
[0048] The thermal shrinkage of the polyester film of the present invention when heated at 150°C for 30 minutes (hereinafter referred to as the thermal shrinkage) is preferably 10% or less in both the MD and TD directions, more preferably 8% or less, and even more preferably 5% or less. A high thermal shrinkage may cause difficulties in printing or coating due to film shrinkage in a printer or coater, or may lead to poor appearance due to film deformation during high-heat processing. In particular, during processing using a printer or coater, the film is not restrained between rollers transporting the film, so shrinkage in the width direction (TD) is likely to occur, potentially resulting in poor appearance. While a lower thermal shrinkage is preferred, due to technical difficulties, the lower limit is, for example, 0.01%.
[0049] In the present invention, the oxygen permeability of the polyester film at a temperature of 23°C and a humidity of 65% is not particularly limited, but is preferably 0.1 mL / m 2 / day / MPa or above and 1000mL / m 2 / day / MPa or less, more preferably 0.1mL / m 2 / day / MPa or above and 200mL / m 2 / day / MPa or less, more preferably 0.1mL / m 2 / day / MPa or above and 120mL / m 2 / day / MPa or less, more preferably 0.1mL / m 2 / day / MPa or above and 100mL / m 2 / day / MPa or less. If it is greater than 1000mL / m 2 / day / MPa, when used as a packaging film, the oxygen that permeates the film may degrade the material or reduce the shelf life of the food. In addition, from the perspective of film manufacturing, the lower limit may be 0.1mL / m 2 / day / MPa. It should be noted that the oxygen permeability can be further improved by applying printing, coating, or co-extrusion to the film.
[0050] In the polyester film of the present invention, the polyester containing furandicarboxylic acid units itself has high oxygen barrier properties (low oxygen permeability). By forming a polyester film that satisfies the stretching step described below or by including a thin film layer mainly composed of an inorganic compound, the oxygen barrier properties are further improved.
[0051] In the present invention, the water vapor transmission rate of the polyester film at a temperature of 37.8° C. and a humidity of 90% is not particularly limited, but is preferably 0.1 g / m 2 / day or more and 40g / m 2 / day or less, more preferably 30g / m 2 / day or less, more preferably 20g / m 2 / day or less. If it is greater than 40g / m 2 / day, there is a risk that the water vapor that permeates the membrane will deteriorate the substance or reduce the shelf life of the food. 2 Note that the water vapor transmission rate can be further improved by applying printing, coating, or co-extrusion to the film.
[0052] In the polyester film of the present invention, the polyester containing furandicarboxylic acid units itself has high water vapor barrier properties (low water vapor permeability). By forming a polyester film that satisfies the stretching step described below or by providing a thin film layer mainly composed of an inorganic compound, the water vapor barrier properties can be further improved.
[0053] The polyester film of the present invention preferably has a breaking strength of 75 MPa or greater in both the MD and TD directions. The breaking strength is more preferably 100 MPa or greater in both the MD and TD directions, further preferably 150 MPa or greater, particularly preferably 200 MPa or greater, and most preferably 220 MPa or greater. If the breaking strength is less than 75 MPa, the film's mechanical strength may be insufficient, leading to the risk of problems such as elongation and misalignment during film processing. Considering manufacturing considerations, the upper limit of the breaking strength is 1000 MPa or less.
[0054] The polyester film of the present invention preferably has an elongation at break of 10 to 300% in both the MD and TD directions. If the elongation at break is less than 10%, there is a risk that the film's mechanical elongation will be insufficient, leading to problems such as cracking and rupture during film processing. Furthermore, for manufacturing reasons, the upper limit of the elongation at break is preferably 300% or less. The elongation at break is more preferably 15 to 150% in both the MD and TD directions, further preferably 20 to 100%, and particularly preferably 30 to 80%.
[0055] The friction coefficient of the polyester film of the present invention is not particularly limited, but the static friction coefficient (μs) is preferably 1.0 or less, and the dynamic friction coefficient (μd) is preferably 1.0 or less. The static friction coefficient (μs) is more preferably 0.8 or less, and even more preferably 0.6 or less. The dynamic friction coefficient (μd) is more preferably 0.8 or less, and even more preferably 0.6 or less. If the static friction coefficient (μs) or the dynamic friction coefficient (μd) exceeds 1.0, there is a risk of deterioration in lubricity and scratches and wrinkles due to friction during film transfer. It should be noted that the static friction coefficient (μs) is the static friction coefficient between one surface and the other surface of the laminated polyester film of the present invention, and the dynamic friction coefficient (μd) is the dynamic friction coefficient between one surface and the other surface of the polyester film of the present invention.
[0056] The polyester film of the present invention preferably has a total light transmittance of 75% or greater. A total light transmittance of 75% or greater can improve the accuracy of detecting internal foreign matter that could cause film defects. The total light transmittance is more preferably 80% or greater, even more preferably 85% or greater, particularly preferably 88% or greater, and most preferably 88.5% or greater. To improve the accuracy of detecting internal foreign matter that could cause film defects, a higher total light transmittance is preferred. However, a total light transmittance of 100% is technically difficult to achieve, and the upper limit is, for example, 98%.
[0057] The lower limit of the 15 μm equivalent impact strength of the polyester film of the present invention is not particularly limited, but is preferably 0.4 J / 15 μm, more preferably 0.6 J / 15 μm, and even more preferably 0.8 J / 15 μm. If it is less than 0.4 J / 15 μm, the strength may be insufficient when used as a bag. The upper limit of the impact strength (impact resistance) is preferably 3.0 J / 15 μm. If it exceeds 3.0 J / 15 μm, the improvement effect becomes saturated.
[0058] The polyester film of the present invention has a thickness of 1 to 300 μm, preferably 5 to 200 μm, more preferably 10 to 100 μm, and even more preferably 10 to 40 μm. A thickness exceeding 300 μm can lead to cost issues and, when used as a packaging material, can reduce visual visibility. Furthermore, a thickness below 1 μm may result in reduced mechanical properties and the risk of not being able to function as a film.
[0059] The cyclic dimer content (the amount of cyclic dimers relative to the total polyester film of the present invention) in the polyester film of the present invention is preferably 1.05% by mass or less. It is more preferably 1.0% by mass or less, even more preferably 0.9% by mass or less, and particularly preferably 0.8% by mass or less. The present inventors have discovered that cyclic dimers precipitated on the film surface serve as nuclei for foreign matter, causing film whitening. When the cyclic dimer content is 1.05% by mass or less, cyclic dimers are less likely to precipitate during post-processing steps, thus contaminating the process and, therefore, are less likely to cause problems even with processes such as printing and lamination. Furthermore, it is known that even when heated, the amount of cyclic dimers precipitated on the film is low, thus preventing film whitening. The details of the cyclic dimer content determination method will be described later. Measurements were made using HPLC analysis, but similar values were obtained using NMR.
[0060] The polyester film of the present invention may have a single layer or a multilayer laminated structure, but preferably has a laminated structure of three or more layers. For example, if the outermost layers are layers B and D, and the layers other than the outermost layer are layers A and C, the layer structure in the film thickness direction may be structures such as B layer / A layer / B layer, B layer / A layer / D layer, B layer / A layer / C layer / B layer, B layer / A layer / C layer / D layer, or B layer / A layer / C layer / A layer / B layer. The resin compositions of layers A to D may be the same or different, but preferably, the resin compositions of the layers are the same, or a structure of B layer / A layer / B layer (two types of three-layer structures) is used. The method for producing a laminated polyester film is not particularly limited, and for example, it can be produced by coextrusion.
[0061] As described above, polyesters with reduced cyclic dimer content can be used in all film layers, but it is preferred to use polyesters with reduced cyclic dimer content on at least one surface, and more preferably on both surfaces. The cyclic dimer content on at least one surface (preferably both surfaces) is preferably 1.0% by mass or less, more preferably 0.9% by mass or less, and even more preferably 0.8% by mass or less. As another preferred embodiment, even when the cyclic dimer content in the entire film exceeds 0.9% by mass (preferably greater than 0.9% by mass and less than 1.5% by mass), surface cyclic dimer precipitation can be suppressed by limiting the surface cyclic dimer content to 0.9% by mass or less (preferably 0.8% by mass or less). The lower the cyclic dimer content, the better, but due to technical difficulties, the cyclic dimer content on at least one surface (preferably both surfaces) is preferably 0.2% by mass or greater. It should be noted that the "surface cyclic dimer content" refers to the cyclic dimer content from the surface to a thickness of 1 μm.
[0062] As described above, the polyester film of the present invention may contain additives. When the polyester film has a multi-layer laminate structure, a polyethylene furandicarboxylate resin layer containing the additive may be used only in the surface layer. Such a film may, for example, have a three-layer structure (b / a / b) in which surface layers (b layers) containing the additive are laminated on both sides of a center layer (a layer) by coextrusion. Alternatively, a three-layer structure (b / c / b) may be used in which the additive is contained in both the center layer (c layer) and the surface layers, with the additive concentrations varying between the layers.
[0063] <Production Method of Polyester Resin>
[0064] Hereinafter, a method for producing the polyester resin for producing the polyester film of the present invention will be described, but the method is not limited to the following method.
[0065] The polyester resin used in the present invention can be produced by performing melt polymerization, followed by preliminary crystallization, and then solid phase polymerization, thereby reducing the amount of cyclic dimers in the polyester resin.
[0066] <Melt polymerization of polyester resin>
[0067] The temperature, time, pressure and other conditions in the esterification reaction of dicarboxylic acid and diol and the ester exchange reaction of dicarboxylic acid ester and diol can adopt the range of the manufacturing method of polyester known in the past. The manufacturing method shown in International Publication No. 2021 / 172215 is particularly preferred, but is not limited to the manufacturing method of the above-mentioned communiqué. In International Publication No. 2021 / 172215, a starting mixture comprising 2,5-furandicarboxylic acid or its diester and ethylene glycol is subjected to an esterification reaction to obtain a hydroxyethyl ester composition, and then the hydroxyethyl ester composition is subjected to a polycondensation reaction in the presence of a polycondensation catalyst and under reduced pressure to obtain a polycondensate. It should be noted that the above-mentioned polycondensation catalyst comprises an aluminum compound and a phosphorus compound, and the above-mentioned phosphorus compound comprises one or more compounds selected from a phosphoric acid compound containing an aromatic group and a phosphinic acid compound containing an aromatic group.
[0068] <Preliminary crystallization of polyester resin>
[0069] If the temperature is rapidly raised to the solid-phase polymerization reaction temperature after melt polymerization, the surface of the polyester resin may partially melt, and the resin may stick together into lumps, making it difficult to handle or difficult to carry out the solid-phase polymerization reaction. Therefore, it is preferable to pre-crystallize the surface of the polyester resin by starting heating at around 80-100°C and slowly raising the temperature to around 150-180°C. However, because prolonged pre-crystallization can cause the resin to discolor, pre-crystallization needs to be performed in a short time. It should be noted that in the description of pre-crystallization, "polyester resin" refers to the polyester resin immediately after melt polymerization.
[0070] Considering the impact on subsequent solid-phase polymerization, film formation, and film quality, a preferred pre-crystallization treatment involves heat-treating the polyester resin in the presence of a supercritical inert gas, followed by decompression from the supercritical pressure to atmospheric pressure. The use of a supercritical inert gas is particularly important to suppress the formation of cyclic dimers. It should be noted that to shorten the pre-crystallization time, known methods such as adding a crystallization nucleating agent to the polyester resin and using a solvent to promote crystallization can be appropriately employed.
[0071] Since the inert gas dissolves into the polyester resin and plasticizes it, the crystallization behavior during treatment with an inert gas under high pressure differs from the crystallization behavior under normal atmospheric pressure. Therefore, the heat treatment temperature is preferably set to a temperature between the crystallization temperature -70°C and the crystallization temperature + 10°C, more preferably between the crystallization temperature -60°C and the crystallization temperature, further preferably between the crystallization temperature -35°C or higher and the crystallization temperature -5°C or lower, particularly preferably between the crystallization temperature -30°C or higher and the crystallization temperature -10°C or lower, and most preferably between the crystallization temperature -25°C or higher and the crystallization temperature -15°C or lower. The method for measuring the crystallization temperature will be described later.
[0072] The inert gas is not particularly limited as long as it does not activate the polyester resin. Examples thereof include oxygen, methane, propane, nitrogen dioxide, nitrogen, argon, helium, and carbon dioxide. Of these, carbon dioxide is preferably used. It should be noted that carbon dioxide may react with certain compounds and cannot be used as an inert gas. However, in this specification, the term "inert gas" refers to a gas that does not activate the polyester resin.
[0073] If the pressure during heat treatment is high, the inert gas dissolves in the polyester resin and plasticizes it, resulting in crystallization in a short period of time. Therefore, the pressure during heat treatment is preferably 5 MPa or more, more preferably 8 MPa or more, further preferably 10 MPa or more, particularly preferably 15 MPa or more, and most preferably 18 MPa or more. The upper limit of the pressure during heat treatment is not particularly limited, for example, 50 MPa or less. A reaction vessel that can withstand pressures greater than 50 MPa would require very thick metal thickness, which is unrealistic.
[0074] In order to make the pressure during heat treatment higher than atmospheric pressure, for example, the following method can be cited: the polyester resin is added to a high-pressure reaction container and connected to a gas cylinder, a pump, a pressure relief valve, a pressure gauge, a safety valve, etc. After the high-pressure reaction container is heated to a specified temperature, an inert gas is supplied by a pump, and the pressure is adjusted to a specified value through a pressure relief valve.
[0075] The heat treatment time is preferably 10 minutes or longer, more preferably 15 minutes or longer, further preferably 20 minutes or longer, and particularly preferably 25 minutes or longer. A heat treatment time of 10 minutes or longer allows the inert gas to fully dissolve in the polyester resin. The upper limit of the heat treatment time is not particularly limited, but is, for example, 200 minutes or shorter, preferably 180 minutes or shorter, and more preferably 150 minutes or shorter. If the heat treatment time exceeds 200 minutes, the effect of increasing the degree of crystallinity becomes saturated.
[0076] The time required to reduce the pressure from the supercritical state to the atmospheric pressure is preferably 0.5 to 20 minutes, more preferably 1.5 to 10 minutes, and even more preferably 3 to 5 minutes.
[0077] The decompression rate from the gas pressure in the supercritical state to atmospheric pressure is preferably 1 to 30 MPa / min, more preferably 2 to 25 MPa / min, further preferably 3 to 15 MPa / min, particularly preferably 4 to 10 MPa / min, and most preferably 5 to 7 MPa / min.
[0078] <Solid-phase polymerization of polyester resin>
[0079] The method for solid-phase polymerization is not particularly limited. For example, a method in which the polyester resin obtained in the polycondensation reaction step is heated under an inert gas atmosphere or under reduced pressure can be used. The inert gas used in the pre-crystallization can be appropriately used, and preferably the same inert gas used in the pre-crystallization is used. Solid-phase polymerization can be performed while the polyester resin pellets or powder are allowed to stand or while stirring. Stirring can be performed by installing a stirring blade in the reaction vessel or by shaking the reaction vessel.
[0080] From the perspective of reducing cyclic dimers, the reaction temperature for solid-phase polymerization is preferably as high as possible, preferably 180°C or higher, more preferably 190°C or higher. The upper limit of the reaction temperature is the melting point of the polyester resin. The reaction time for solid-phase polymerization is preferably 1 hour or longer, more preferably 3 hours or longer. On the other hand, due to the risk of coloration, the reaction time is preferably 50 hours or shorter, more preferably 40 hours or shorter, and even more preferably 30 hours or shorter.
[0081] <Method for producing polyester film>
[0082] The method for producing the polyester film of the present invention will be described. First, a polyester resin, such as PEF pellets or PEF flakes, is dried or hot-air dried to a moisture content of less than 200 ppm. Next, the raw materials are measured, mixed, and fed into an extruder for melt extrusion to form a sheet. Furthermore, the molten sheet is brought into close contact with a rotating metal roll (casting roll) using electrostatic application and cooled to solidify, resulting in an unstretched film (unstretched sheet).
[0083] Furthermore, high-precision filtration can be performed to remove foreign matter contained in the molten resin, while maintaining the molten resin at a temperature between the melting point + 5°C and the melting point + 60°C. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a sintered stainless steel filter material is preferred due to its excellent performance in removing aggregates primarily composed of Si, Ti, Sb, Ge, and Cu, as well as high-melting-point organic matter.
[0084] In the case of forming a laminated structure of three or more layers by coextrusion, two or more extruders are used to extrude the raw materials for each layer. A multi-layer feed head (for example, a confluence head with a square confluence section (Japanese: 合流ブロック)) is used to make two layers converge, and it is extruded into a sheet from a slit-shaped die, and then cooled and solidified on a casting roll to produce an unstretched film. Alternatively, a manifold die can be used instead of the multi-layer feed head.
[0085] Even when pre-crystallization and solid-phase polymerization are carried out to reduce the amount of cyclic dimers in the polyester resin, the amount of cyclic dimers increases during the process of melting the polyester resin and melt-extruding it into a sheet. Therefore, it is also important to suppress the increase in the amount of cyclic dimers in the process of manufacturing a film using a polyester resin. If the time from when the resin contacts the screw of the extruder until melting occurs and the sheet-shaped resin is extruded from the die is defined as the melt line residence time (Japanese: メルトライン滞留時間), then by shortening the melt line residence time, thermal decomposition during melt extrusion is suppressed, and thus the increase in cyclic dimers can be suppressed. The melt line residence time is preferably within 10 minutes, more preferably within 8 minutes, further preferably within 5 minutes, and particularly preferably within 3 minutes. There is no particular limitation on the lower limit, but since it is necessary to melt the resin and mix the resins evenly to a certain extent, the substantial lower limit is 1 minute or more.
[0086] The lower the resin temperature of the melt line residence time, the more effectively the regeneration of cyclic dimers during melt extrusion can be suppressed. The resin temperature is preferably at or below the melting point of the polyester resin + 60°C, more preferably at or below the melting point + 55°C. There is no particular limitation on the lower limit, but since it is necessary to melt the resin, the substantial lower limit is at or above the melting point + 5°C.
[0087] Next, the unstretched film obtained by the above method is biaxially stretched and then heat-treated. For example, when biaxially stretching an unstretched film containing furandicarboxylic acid units to produce a biaxially oriented polyester film, the following methods can be used: a sequential biaxial stretching method in which uniaxial stretching is performed in the MD or TD direction, followed by stretching in the orthogonal direction; a simultaneous biaxial stretching method in which stretching is performed simultaneously in the MD and TD directions; or a method in which a linear motor is used as the drive for simultaneous biaxial stretching. In the sequential biaxial stretching method, MD stretching can be performed by applying a speed difference using heated rollers to stretch the film in the MD direction. Infrared heaters, etc., can also be used in conjunction with heating. Subsequent TD stretching can be performed by introducing the MD-stretched sheet into a tenter, holding both ends with clamps, and stretching the film in the TD direction while heating. The TD-stretched film is then heat-treated within the tenter. Heat treatment can be performed while the film is stretched by TD stretching, but it can also be performed while relaxing the film in the TD direction. The heat-treated film may be cut at both ends and wound using a winder.
[0088] (i) Control of the stretch ratio in the MD direction of the film
[0089] To obtain the polyester film of the present invention, it is preferably stretched in the MD direction at a ratio of 2.5 to 10.0. The stretch ratio in the MD direction is more preferably 3.5 times or more, further preferably 3.8 times or more, particularly preferably 4.0 times or more, and most preferably 4.5 times or more. By setting the stretch ratio in the MD direction to 2.5 times or more, a film having excellent mechanical properties such as a ΔP of 0.100 or more, a film breaking strength of 100 MPa or more, and a film breaking elongation of 15% or more can be produced. A stretch ratio in the MD direction of 10.0 times or less is preferred because the frequency of breakage decreases. The higher the stretch ratio in the MD direction, the higher the temperature of the heat setting process can be, and the lower the thermal shrinkage rate.
[0090] (ii) Control of the stretching temperature in the MD direction of the film
[0091] To obtain the polyester film of the present invention, stretching in the MD direction is preferably performed at a temperature of 90°C to 150°C. More preferably, it is 100°C to 125°C. A stretching temperature of 90°C or higher in the MD direction is preferred because the frequency of breakage decreases. A stretching temperature of 150°C or lower in the MD direction is preferred because uniform stretching is achieved.
[0092] (iii) Control of the stretch ratio in the TD direction of the film
[0093] To obtain the polyester film of the present invention, it is preferably stretched in the TD direction at a ratio of 2.5 to 10.0. The TD stretch ratio is more preferably 3.0 times or greater, further preferably 3.5 times or greater, particularly preferably 4.0 times or greater, and most preferably 4.5 times or greater. By setting the TD stretch ratio to 2.5 times or greater, a film having excellent mechanical properties, such as a ΔP of 0.100 or greater, a film breaking strength of 100 MPa or greater, and a film breaking elongation of 15% or greater, can be produced. A TD stretch ratio of 10.0 times or less is preferred because the frequency of breakage is reduced.
[0094] (iv) Control of stretching temperature in the TD direction
[0095] To obtain the polyester film of the present invention, stretching in the TD direction is preferably performed at a temperature of 80°C to 200°C. More preferably, it is 95°C to 135°C. A TD stretching temperature of 80°C or higher is preferred because the frequency of breakage decreases. A TD stretching temperature of 200°C or lower is preferred because uniform stretching is possible.
[0096] (v) Control of the thermal fixation temperature of the film
[0097] To obtain the polyester film of the present invention, a heat setting treatment is preferably performed at a temperature of 110°C to 220°C. A heat setting temperature of 220°C or lower is preferred because the film is less likely to become opaque and the frequency of melt fracture decreases. Increasing the heat setting temperature is preferred because it reduces thermal shrinkage. A temperature of 120°C or higher is more preferred, 140°C or higher is even more preferred, 160°C or higher is even more preferred, 175°C or higher is particularly preferred, and 185°C or higher is most preferred. Heat setting tends to increase the plane orientation coefficient ΔP. Furthermore, the heat setting temperature is more preferably 210°C or lower.
[0098] (vi) Control of film thermal fixation time
[0099] To obtain the polyester film of the present invention, the heat setting treatment is preferably performed for 5 to 20 seconds, more preferably 7 to 15 seconds, and even more preferably 8 to 12 seconds. The length of the heat setting time affects the plane orientation coefficient ΔP.
[0100] (vii) Control of relaxation temperature in the TD direction
[0101] To obtain the polyester film of the present invention, a relaxation treatment is preferably performed in the TD direction at 100°C to 200°C. The relaxation temperature in the TD direction is more preferably 165°C to 195°C, and even more preferably 175°C to 195°C. Relaxation at such a relaxation temperature can reduce the thermal shrinkage.
[0102] (viii) Control of relaxation rate in TD direction
[0103] In order to obtain the polyester film of the present invention, the relaxation rate in the TD direction is preferably 0.5% to 10.0%, more preferably 2% to 6%. By relaxing at the above relaxation temperature, the heat shrinkage rate can be reduced.
[0104] During or after the stretching process, the film may be subjected to a corona treatment or plasma treatment. Furthermore, by appropriately mixing resins, crosslinking agents, particles, etc., dissolving them in a solvent, and then applying the resulting solution or dispersion, it is possible to impart properties such as slip, anti-blocking, antistatic, and adhesion.
[0105] Furthermore, the function can be improved by subjecting the film to surface treatment after stretching and heat treatment, for example, printing, coating, etc.
[0106] Furthermore, by laminating a stretched, heat-treated, or surface-treated film to paper, the film can be used for packaging, labels, design sheets, and the like.
[0107] This application claims the benefit of priority based on Japanese Patent Application No. 2023-048171, filed on March 24, 2023. The entire contents of the specification of Japanese Patent Application No. 2023-048171, filed on March 24, 2023, are incorporated herein by reference.
[0108] Example
[0109] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples. The evaluation methods used in each example and comparative example are as follows.
[0110] Evaluation Method
[0111] (1) Intrinsic viscosity (IV)
[0112] The polyester resin or polyester film is pulverized and dried, then dissolved in a 75 / 25 (mass ratio) mixture of p-chlorophenol and tetrachloroethane. Using an Ubbelohde viscometer, the flow time of a 0.4 g / dl solution and the flow time of the solvent alone are measured at 30°C. The intrinsic viscosity of the polyester resin or polyester film is calculated based on the ratio of these times using the Huggins equation, assuming a Huggins constant of 0.38.
[0113] (2) Crystallization temperature, melting point, and glass transition temperature
[0114] The crystallization temperature, melting point, and glass transition temperature of the polyester resin were measured using a differential scanning calorimeter (DSC214 Polyma) manufactured by NETZSCH JAPAN.
[0115] (3) Film thickness
[0116] Using a Millitron, four 5 cm square samples were cut from four random locations on the film to be measured. Five locations on each sample (20 locations in total) were measured, and the average value was defined as the film thickness.
[0117] (4) Breaking strength and elongation at break
[0118] The film samples were cut into strips 140 mm long and 10 mm wide in the MD and TD directions, respectively, using a single-edged razor. The strips were then stretched using an AUTOGRAPH AG-IS (manufactured by Shimadzu Corporation). The resulting load-strain curves were used to determine the breaking strength (MPa) and elongation (%) in each direction. The measurements were performed at 25°C, with a chuck distance of 40 mm, a crosshead speed of 100 mm / min, and a dynamometer load of 1 kN. The breaking strength and elongation were measured five times each, and the average values were used as the breaking strength and elongation of the film.
[0119] (5) Refractive index and plane orientation coefficient ΔP
[0120] Using an Abbe refractometer according to JIS K 7142-1996 5.1 (Method A), using sodium D-rays as the light source, the film's refractive index nx in the MD direction, the refractive index ny in the direction perpendicular to the MD direction, and the refractive index nz in the thickness direction were measured. The plane orientation coefficient ΔP was calculated using the following formula. Three measurements were performed, and the average of these measurements was used as the film's refractive index and plane orientation coefficient ΔP. Note that diiodomethane was used as the sealing liquid.
[0121] ΔP={(nx+ny)-2nz} / 2
[0122] (6) Total light transmittance and haze
[0123] The measurement was performed in accordance with JIS K 7136. As a measuring instrument, a turbidimeter type NDH-5000 manufactured by Nippon Denshoku Industries was used.
[0124] (7) Haze change △Hz
[0125] The film was cut into 50 mm squares and the haze (haze value) before heating was measured according to JIS K 7105 "Test methods for optical properties of plastics" (Haze value). The measuring instrument used was a NDH-300A turbidimeter manufactured by Nippon Denshoku Industries. After the measurement, the film was placed in an oven heated to 150°C. After 30 minutes, the film was removed and the haze of the film was measured using the same method as for Hz0 to obtain the haze value after heating (Hz). 30 (%). Will be from Hz 30 Subtract the value obtained by Hz0 (Hz 30 -Hz0) is set to △Hz (%).
[0126] (8) Thermal shrinkage in MD and TD directions
[0127] The film was cut so that the measured direction was 250 mm and the perpendicular direction was 10 mm. Marks were placed at 150 mm intervals in the measured direction. The interval between the marks was measured under a constant tension of 5 gf, and this interval was designated as A (mm). The cut film was then placed in an oven at 150°C and heated at 150±3°C for 30 minutes without a load. The interval between the marks was then measured under a constant tension of 5 gf, and this interval was designated as B (mm). Using the values of A and B, the thermal shrinkage ratio was calculated using the following formula.
[0128] Thermal shrinkage (%) = (AB) / A×100
[0129] (9) The amount of cyclic dimers contained in the entire membrane
[0130] A polyester film was finely ground, and 50 mg was dissolved in 1.5 mL of a mixed solvent of hexafluoroisopropanol (HFIP) and chloroform (2 / 3 by volume). To the resulting solution, 10 mL of chloroform was added and mixed evenly. 5 mL of methanol was added to the resulting mixture to precipitate the polymer. The mixture was then filtered, and the filtrate was concentrated to dryness using a rotary evaporator. 5 mL of dimethylformamide was added to the concentrated solid, and the filtrate was subjected to HPLC analysis to quantify the amount of cyclic dimer.
[0131] HPLC analysis conditions
[0132] Device: UFLC manufactured by Shimadzu Corporation
[0133] Chromatographic column: Imtakt Cadenza CD-C18 3μm2×150mm
[0134] Mobile phase: A 0.1% formic acid, B acetonitrile
[0135] 0min (5%B)-18 (35)-45 (60)-50 (100)-55 (100)-55.01 (5)-60 (5)
[0136] Flow rate: 0.4 mL / min
[0137] Column temperature: 50°C
[0138] Injection volume: 5 μL
[0139] Detection wavelength: 258nm
[0140] (10) Amount of cyclic dimers on the membrane surface
[0141] The polyester film was scraped from the surface to a thickness of 1 μm, and the amount of cyclic dimers on the film surface was quantified using the same method as in (9) above.
[0142] (11) Color coordinate b value
[0143] The evaluation was performed using a ZE6000 colorimeter manufactured by Nippon Denshoku Industries Co., Ltd. Ten films were stacked and reflection was measured using a white plate. The values were rounded off to the second decimal place and the resulting values were designated as color coordinates b. value.
[0144] <Polyester raw materials>
[0145] (1) Production method of PEF-A
[0146] To a starting mixture of 2,5-furandicarboxylic acid (FDCA) and ethylene glycol (EG) (EG / FDCA molar ratio of 1.5), 149 ppm of tetraethylammonium hydroxide (calculated as molar ppm of N(Et)4OH based on the molar amount of FDCA) was added. Esterification was carried out over 3.2 hours while the temperature of the mixture was gradually raised from 80°C to 220°C. After distilling off volatile compounds such as water, a polycondensation catalyst and a phosphorus compound were added. A basic aluminum acetate solution in ethylene glycol was used as the polycondensation catalyst, and a solution of diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate in ethylene glycol was used as the phosphorus compound. The aluminum content was 202 ppm, and the diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate content was 435 ppm, based on the molar amount of FDCA in the starting mixture. The temperature was raised from 220°C to 270°C, and the pressure was reduced to 1 mmHg (approximately 133 Pa), allowing for 60 minutes of initial polycondensation. Further, a post-condensation reaction was carried out at approximately 13 Pa and 270°C for 119 minutes. At the end of the polycondensation, the pressure was returned to normal, and the polycondensate was passed into water in the form of strands. After cooling, it was cut into pellets. These pellets (raw material) were designated PEF-A. PEF-A has an intrinsic viscosity of 0.62 dL / g, a crystallization temperature of 170°C, a melting point of 215°C, a glass transition temperature of 86°C, and a cyclic dimer content of 1.1% by mass.
[0147] (2) Manufacturing method of PEF-B
[0148] PEF-A was dried under reduced pressure (1 Torr) at 80°C for 12 hours and then placed in a reaction vessel. Carbon dioxide was delivered by a pump connected to a carbon dioxide cylinder, and the pressure in the reaction vessel was adjusted to 20 MPa using a pressure relief valve. Pre-crystallization was then performed at 150°C for 30 minutes. After pre-crystallization, the pressure was reduced to atmospheric pressure at 5 MPa / min, and solid-phase polymerization was performed at 190°C for 24 hours to produce PEF-B. PEF-B had an intrinsic viscosity of 0.90 dL / g and a cyclic dimer content of 0.43% by mass.
[0149] (3) Manufacturing method of PEF-C
[0150] PEF-C was obtained by polymerization in the same manner as PEF-A, except that 0.05% by mass of silica particles (Sylysia 310, manufactured by Fuji Slysia Chemical Co., Ltd., average particle size 2.7 μm) were added as an additive. PEF-C had an intrinsic viscosity of 0.62 dL / g, a crystallization temperature of 170°C, a melting point of 215°C, a glass transition temperature of 86°C, and a cyclic dimer content of 1.1% by mass.
[0151] (4) Manufacturing method of PEF-D
[0152] PEF-C was dried under reduced pressure (1 Torr) at 80°C for 12 hours and then placed in a reaction vessel. Carbon dioxide was delivered by a pump connected to a carbon dioxide cylinder, and the pressure in the reaction vessel was adjusted to 20 MPa using a pressure relief valve. Pre-crystallization was then performed at 150°C for 30 minutes. After pre-crystallization, the pressure was reduced to atmospheric pressure at 5 MPa / min, and solid-phase polymerization was performed at 190°C for 24 hours to produce PEF-D. The intrinsic viscosity of PEF-D was 0.90 dL / g, and the cyclic dimer content was 0.43% by mass.
[0153] (Example 1)
[0154] PEF-D was used as the raw material. After drying under reduced pressure (1 Torr) at 100°C for 24 hours to a moisture content of 80 ppm, it was supplied to a twin-screw extruder (screw diameter 30 mm, L / D = 25). The resin temperature in the extruder's melt section, kneading section, piping, and gear pump (the resin temperature up to the gear pump) was set to 268°C, and in the piping after the gear pump to 270°C. The material was melt-extruded into a sheet through a T-die (die head). The time from the resin contacting the extruder screw until the sheet-shaped resin was extruded from the die (hereinafter referred to as the melt line residence time) was 3 minutes.
[0155] The extruded resin was then cast on a cooling drum having a surface temperature of 20° C., adhered to the surface of the cooling drum by electrostatic application, and cooled and solidified to produce an unstretched film having a thickness of 300 μm.
[0156] The resulting unstretched film was heated to 120°C using a roller set, then stretched to 5x in the MD direction using a roller set with a differential circumferential speed. The film was then introduced into a tenter and held with clamps. TD stretching was performed at a temperature of 105°C and a TD stretch ratio of 5x. Subsequently, the film was heat treated at 200°C for 12 seconds and then relaxed at 190°C for 5% to obtain a polyester film. The cyclic dimer content in the entire polyester film and on the film surface was 0.66% by mass (0.33 mol%). The physical properties of the resulting polyester film are shown in Table 2.
[0157] (Examples 2 to 5, Comparative Examples 1 to 3)
[0158] A polyester film was obtained by the same method as in Example 1 except that the polyester raw materials shown in Table 1 were used and the resin temperature and melt line residence time before the filter were changed to the conditions shown in Table 1. The physical properties of the obtained polyester film are shown in Table 2.
[0159] (Example 6)
[0160] As the raw material for the surface layer (layer B), PEF-B was dried at 100°C under reduced pressure (1 Torr) for 24 hours before being supplied to extruder 1. Separately, as the raw material for the intermediate layer (layer A), PEF-A was dried at 100°C under reduced pressure (1 Torr) for 24 hours before being supplied to extruder 2. The resin temperature (resin temperature up to the filter) in the extruders' melting section, kneading section, polymerization tube, gear pump, and filter was set to 268°C, and in the subsequent polymerization tube to 270°C. Layers were stacked using a three-layer confluence head in a B / A / B configuration, and the resin was melt-extruded from the die head into a sheet. The gear pumps for each layer were controlled to maintain a thickness ratio of B / A / B = 20 / 60 / 20. The melt line residence time was 3 minutes.
[0161] After melt-extruding the sheet-like resin, a polyester film was obtained by the same production method as in Example 1. Table 2 shows the physical properties of the obtained polyester film.
[0162] (Examples 7-8, Comparative Example 4)
[0163] A polyester film was obtained by the same method as in Example 6 except that the polyester raw materials shown in Table 1 were used and the thickness ratio of each layer, the resin temperature up to the filter, and the melt line residence time were changed to the conditions shown in Table 1. The physical properties of the obtained polyester film are shown in Table 2.
[0164] [Table 1]
[0165]
[0166] [Table 2]
[0167]
[0168] Industrial applicability
[0169] The polyester film of the present invention has a low content of cyclic dimers and is less likely to lose transparency even when heated, despite using biomass-derived furandicarboxylic acid. Therefore, the polyester film can be suitably used as an industrial film or a packaging film.
Claims
1. A polyester film comprising a dicarboxylic acid component mainly composed of furandicarboxylic acid and a diol component mainly composed of ethylene glycol, wherein the polyester film satisfies the following necessary conditions (1) to (3): (1) The plane orientation coefficient ΔP is greater than or equal to 0.100 and less than or equal to 0.170; (2) The haze of the polyester film is less than 15%; (3) The haze of the polyester film is denoted as Hz0, and the haze after heating the polyester film at 150° C. for 30 minutes is denoted as Hz. 30 When Hz is satisfied 30 -Hz0≤15, the Hz0 and Hz 30 In %.
2. The polyester film according to claim 1, further satisfying the following necessary condition (4): (4) The content of cyclic dimers is 1.0% by mass or less.
3. The polyester film according to claim 1, further satisfying the following requirements (5) and (6): (5) Having a stacked structure of more than three layers; (6) The content of the cyclic dimer in at least one surface is 1.0% by mass or less.
Citation Information
Patent Citations
Drying / deodorizing device of printer
JP1989040336A
Polyester resin and molding comprising polyester resin
JP2022155579A
Machine learning apparatus, machine learning method, and machine learning program
JP2023048171A
Method for producing polyester and polyester produced by said method
WO2021172215A1